Mechanism and security of UV driven sodium percarbonate for sulfamethoxazole degradation using DFT and metabolomic analysis. (15th April 2023) - Yu, Xiaolong; Jin, Xu; Li, Meng; Yu, Yuanyuan; Liu, Hang; Zhou, Rujin; Yin, Aiguo; Shi, Junyi; Sun, Jianteng; Zhu, Lizhong
Abstract: Recently, sodium percarbonate (SPC) as a solid substitute for H2 O2 has aroused extensive attention in advanced oxidation processes. In current work, the degradation kinetics and mechanisms of antibiotic sulfamethoxazole (SMX) by ultraviolet (UV) driven SPC system were explored. The removal efficiency of SMX was enhanced as the increasing dosage of SPC. Moreover, hydroxyl radical (OH), carbonate radical (CO3 − ) and superoxide radical (O2 − ) were verified to be presented by scavenger experiments and OH, CO3 − exhibited a significant role in SMX degradation. Reactions mediated by these radicals were affected by anions and natural organic matters, implying that an incomplete mineralization of SMX would be ubiquitous. The screening four intermediates and transformation patterns of SMX were verified by DFT analysis. Metabolomic analysis demonstrated that a decreasing negative effect in E. coli after 24 h exposure was induced by intermediates products. In detail, SMX interfered in some key functional metabolic pathways including carbohydrate metabolism, pentose and glucuronate metabolism, nucleotide metabolism, arginine and proline metabolism, sphingolipid metabolism, which were mitigated after UV/SPC oxidation treatment, suggesting a declining environmental risk of SMX. This work provided new insights into biological impacts of SMX and its transformation products and vital guidance for SMX pollution control using UV/SPC technology. Graphical abstract: Image 1 Highlights: UV/SPC system exhibited a good performance on SMX degradation. Intermediates and transformation patterns were analyzed by DFT calculation. OH and CO3 . − as primary reactive species were responsible for SMX degradation. Interference on metabolism of E. coli was mitigated by intermediates mixture of SMX. A moderate mineralization should be considered in actual water remediation.